WOMEN IN THE CRIMINAL JUSTICE SYSTEM IN INDONESIA: STUDI OF GENDER DISCRIMINATION IN THE CRIMINAL PROCEDURE CODE - Lysa Angrayni; Febri Handayani; Syafrinaldi; Ellydar Chaidir; Efendi Ibnu Susilo (International Conference On Law And Social Sciences, 2024)
This article is based on the idea that Indonesia as a legal state must accommodate everyone's rights, including the rights of women without exception. Every woman who encounters the law, especially criminal law, has the right to obtain access to justice in the criminal justice system as a form of protection for women as a vulnerable group. The criminal procedural law that is currently being developed is not accountable because of the high values of patriarchy and masculinity that are still rooted in people's lives, including in the formation of laws. Women often experience discriminatory actions both in the pre-adjudication stage and at the adjudication stage. The issue of gender justice is significant to discuss to create a society that is just and not gender biased. This research aims to analyze the current state of gender inequality for women in the criminal justice system in Indonesia and highlight the potential for improvement. By taking stock of the treatment conditions for women in the criminal justice system, the study also aims to provide valuable insight into women's challenges and highlight best practices for improving gender justice. It is hoped that the findings of this research will analyze the substantial gaps in gender justice issues in the Indonesian criminal justice system, including bias in the legal framework and gender stereotypes that influence the decision-making process. This research will also identify and analyze best practices from other countries, where gender justice has been successfully integrated into the criminal justice system, offering potential solutions for improvement in Indonesia. By highlighting existing gaps and exploring best practices from other countries, this research aims to provide recommendations to policymakers, legal experts, and organizations to improve gender equity for women.